Academic writing : a handbook for international students - Bailey, Stephen (London ; New York : Routledge, 2006)
This book is a new kind of writing course for all international students who have to write exams or coursework in English. This practical book explains the writing process and covers all the key writing skills.
Includes bibliographical references.
osc 30/05/13
Loans
Keywords: English language - writing process; English language; Academic writing